SEMANTIC SHIFT IN CONTEMPORARY LANGUAGE USE: AN APPLIED LINGUISTIC STUDY (American Journal of Research in Humanities and Social Sciences, 2026)
This research aims to study the phenomenon of semantic shift in contemporary Arabic linguistic usage, as one of the active semantic phenomena that contribute to the construction and direction of meaning within discourse. The research is based on the hypothesis that semantic shift is not a random departure from lexical meaning, but rather a semantic transition governed by the constraints of context, situation, and the function of the discourse.